Transfer Properties of Ethanol-Amino Acid-Water System at Different Temperatures - Shrivastava, Anjali (Asian Journal of Chemistry, 2010)
The densities of sodium chloride, glycine and dl-alanine were measured in aqueous ethanol solution at different temperatures. The concentration of sodium chloride, glycine and dl-alanine varied from 0.01 to 0.1 molar. In this range transfer functions of electrolyte from water to ethanol solution are found to be identical to complementary transfer functions of ethanol from water to electrolyte solutions. Volume of transfer is found to increase with increase in temperature.